ACTIVITY OF PHENOL OF Morinda citrifolia AS NATURAL ANTIBACTERIA TO INHIBIT THE GROWTH OF MASTITIS-ASSOCIATED BACTERIA - Theresia Ika Purwantiningsih; Yuni Suranindyah; Widodo Widodo (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
Most of dairy farmers less of attention about sanitation after milking. It can trigger a disease, mastitis. Mastitis is one of harmful disease in dairy cow, because it can decrease quality and quantity of milk. The aim of this study was to determine active compounds in the noni fruit extract, to measure the levels of phenolic compounds in different stage of fruit maturity and to know the result of California Mastitis Test (CMT) test between teat’s cow were dipped with noni fruit extract and commercial teat dipping solution containing 1.25% iodine (commercial). The highest level of phenols was presented in ripe noni fruit. Based on statistical analysis using One Way Anova followed by Duncan's test Multiply Range Test (DMRT), there were significant differences (P<0.05) in CMT test between teat’s cow were dipped in noni fruit extract and iodine 1.25% solution. Noni fruit extract solution showed better result than commercial dipping solution containing iodine. The conclusion is noni fruit extract contains natural antibacteria, it can be used to teat dipping solution.